2013
DOI: 10.1371/journal.pone.0064594
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genome-Wide Survey, Genomic Constitution and Expression Profiling of the NAC Transcription Factor Family in Foxtail Millet (Setaria italica L.)

Abstract: The NAC proteins represent a major plant-specific transcription factor family that has established enormously diverse roles in various plant processes. Aided by the availability of complete genomes, several members of this family have been identified in Arabidopsis, rice, soybean and poplar. However, no comprehensive investigation has been presented for the recently sequenced, naturally stress tolerant crop, Setaria italica (foxtail millet) that is famed as a model crop for bioenergy research. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 90 publications
(110 reference statements)
13
106
0
Order By: Relevance
“…We identified 143 NAC genes in G. arboreum and 145 in G. raimondii by analyzing the NAC TF structure domain. Comprehensive analyses revealed that members of the NAC-TF family varied both in monocots or dicots (Ji et al, 2003;Rushton et al, 2008;Shen et al, 2009;Hu et al, 2010;Finn et al, 2011;Lee et al, 2012;Puranik et al, 2013;Shah et al, 2013;Shang et al, 2013;Zhu et al, 2013;Cao et al, 2015;You et al, 2015), for example, the distribution of NAC-TFs in dicots ranges from 79 in C. paraya to 187 in E. grandis. However, compared to the ~105 NAC-TFs in A. thaliana, C. papaya, and T. cacao, which belong to the malvid family, diploid cotton shows a significantly higher number of NAC-TFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 143 NAC genes in G. arboreum and 145 in G. raimondii by analyzing the NAC TF structure domain. Comprehensive analyses revealed that members of the NAC-TF family varied both in monocots or dicots (Ji et al, 2003;Rushton et al, 2008;Shen et al, 2009;Hu et al, 2010;Finn et al, 2011;Lee et al, 2012;Puranik et al, 2013;Shah et al, 2013;Shang et al, 2013;Zhu et al, 2013;Cao et al, 2015;You et al, 2015), for example, the distribution of NAC-TFs in dicots ranges from 79 in C. paraya to 187 in E. grandis. However, compared to the ~105 NAC-TFs in A. thaliana, C. papaya, and T. cacao, which belong to the malvid family, diploid cotton shows a significantly higher number of NAC-TFs.…”
Section: Discussionmentioning
confidence: 99%
“…They also play an important role in plant development, and are involved in osmotic stress and various plant developmental processes. In recent years, genomic analyses of the NAC gene family have been conducted in angiosperms such as Arabidopsis thaliana (Ooka et al, 2003), Oryza sativa (Fang et al, 2008;Nuruzzaman et al, 2010), Vitis vinifera (Wang et al, 2013), Populus trichocarpa (Hu et al, 2010), Glycine soja , Setaria italic (Puranik et al, 2013), Gossypium raimondii (Shang et al, 2013), and Musa acuminata (Cenci et al, 2014). As one of the largest groups of plant transcription factors (TFs), the NAC-TF family consists of several genes in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the above candidate genes from millet crops are transcription factors (TFs) as they can regulate the expression of downstream stress responsive genes and thus play important role in imparting stress tolerance. Of note, several candidate TFs including AP2/ERFs, NAC, C 2 H 2 zinc finger and MYB were analyzed in foxtail millet to identify suitable candidate genes which can be used for further characterization using transgene-based approaches towards engineering stress resistance (Lata et al, 2014;Puranik et al, 2013;Muthamilarasan et al, 2014b;Muthamilarasan et al, 2014c). In addition to TFs, several stress-responsive genes such as WD40, Dicer-like (DCL), Argonaute (AGO) and RNAdependent RNA polymerases (RDR) have been studied in foxtail millet to identify potential candidate genes for downstream characterization (Mishra et al, 2014;Yadav et al, 2014c).…”
Section: Functional Genomicsmentioning
confidence: 99%
“…Extensive genome-wide investigation and expression profiling studies of various TF families such as AP2/ERFs, NAC, C 2 H 2 zinc finger and MYB (Lata et al, 2014;Puranik et al, 2013;Muthamilarasan et al, 2014b;Muthamilarasan et al, 2014c) and stress responsive genes such as WD40, DCL, AGO and RDR polymerases and ALDH (Mishra et al, 2014;Yadav et al, 2014c;Zhu et al, 2014) have also been carried out in foxtail millet for analyzing gene families implicated in stress tolerance, identifying suitable candidate genes and delineating gene regulatory networks and molecular cross talks for abiotic stress responses.…”
Section: Foxtail Milletmentioning
confidence: 99%